2021
DOI: 10.3389/fmars.2021.720774
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Drivers in Humpback Whale Distribution, Movement and Behavior: A Review

Abstract: Humpback whales, Megaptera novaeangliae, are a highly migratory species exposed to a wide range of environmental factors during their lifetime. The spatial and temporal characteristics of such factors play a significant role in determining suitable habitats for breeding, feeding and resting. The existing studies of the relationship between oceanic conditions and humpback whale ecology provide the basis for understanding impacts on this species. Here we have determined the most relevant environmental drivers id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 198 publications
0
12
0
2
Order By: Relevance
“…and not for thermoregulation, thereby ensuring the survival of the calf (Braithwaite et al, 2015;Meynecke et al, 2021). The energy needs of whales vary according to their sex and reproductive status, being reflected in the temporal variability at the time of arrival to their breeding grounds and in the length of stay (Craig et al, 2003;Avila et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and not for thermoregulation, thereby ensuring the survival of the calf (Braithwaite et al, 2015;Meynecke et al, 2021). The energy needs of whales vary according to their sex and reproductive status, being reflected in the temporal variability at the time of arrival to their breeding grounds and in the length of stay (Craig et al, 2003;Avila et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The energy needs of whales vary according to their sex and reproductive status, being reflected in the temporal variability at the time of arrival to their breeding grounds and in the length of stay (Craig et al, 2003;Avila et al, 2020). In other humpback whale populations, it has been observed that individuals that do not have sufficient energy reserves do not migrate to their breeding grounds so that the abundance of adults and calves decreases in these areas (Frankel et al, 2021;Meynecke et al, 2021;Schall et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine cetacean species observed, no niche separation was apparent, and all species were observed throughout the survey area. This is an interesting finding, since mysticetes such as humpback whales (Meynecke et al 2021), and odontocetes (such as pilot and beaked whales) have differential life-history patterns and diets that may not all be so reliant on environmental drivers, such as Chl-a. For example, pilot whales, which feed predominantly on mesopelagic fish and deepwater squids (Gannon et al 1997), are known to forage close to shelf breaks and submarine canyons, potentially using specialised foraging behaviours for targeting steep bathymetric gradients, meaning that their latitudinal distribution may be limited to regions where this foraging strategy is effective (Thorne et al 2017).…”
Section: Species Sightingsmentioning
confidence: 96%
“…For highly mobile, large animals, such as cetaceans, their distribution and response to a changing environment is influenced by its feeding behaviors, preferences, and flexibilities, along with its physiological needs and tolerances, particularly those of the newborns. For example, Meynecke et al (2021) reviewed over 148 studies to identify humpback whale habitat preferences during their annual cycle. They found in feeding grounds the explanatory covariates included upwelling strength, high chlorophyll-a concentrations, depth and currents.…”
Section: Introductionmentioning
confidence: 99%